A text book of fundamentals of mathematics and statistics paper -I, XI Sci. - Deshpande R., Saptarshi R., Desai N. & etc. (Nirali Prakashan, Pune, 2006)
Stats/Maths
ENGLISH
Keywords: A text book of fundamentals of mathematics and statistics paper -I, XI Sci; Stats/Maths; Stats/Maths